Exploring cooling of PV panels based on metallic and nonmetallic nanofluids: An experimental study - Munzer SY Ebaid; Ayoup M Ghrair; Feras Batarseh; James Roscow; Christopher R Bowen (Advances in Mechanical Engineering, 2024)
An outdoor experimental study investigated the cooling of photovoltaic (PV) panels using nano-fluids containing metallic (calcium carbonate, CaCO 3 ) and non-metallic (ferro-magnetite, Fe 3 O 4 ) particles. The study compared the solar power output and efficiency of PV panels cooled by various nano-fluids, as well as uncooled and water-cooled systems, under laminar and turbulent flow conditions with flow rates ranging from 1000 to 7000 mL/min. Aluminum heat exchangers (460 mm in length, 10 mm in outer diameter, and 10 mm in thickness) were attached to the rear surface of each PV cell, enabling the analysis of cell temperature, thermal performance, and electrical performance. The use of CaCO 3 and Fe 3 O 4 nano-fluids notably reduced the average cell surface temperature compared to uncooled and water-cooled systems. Fe 3 O 4 nano-fluid, in particular, excelled due to its high thermal conductivity, which resulted in an improved heat transfer coefficient and Nusselt number when compared to air and water cooling. The electrical performance, power output, and efficiency of the PV cells all improved when cooling systems were employed in contrast to the uncooled condition. Among the available cooling methods, Fe 3 O 4 nano-fluid stood out for its superior results, thanks to its exceptional thermal conductivity.